Outer membrane protein K of Escherichia coli: purification and pore-forming properties in lipid bilayer membranes. - Whitfield, C (1983)
Protein K, a recently described outer membrane protein correlated with encapsulation in Escherichia coli (Paakkanen et al., J. Bacteriol. 139:835-841, 1979), has been purified to apparent homogeneity. Purification was based upon the noncovalent association of protein K with peptidoglycan, and the purified protein was shown to form sodium dodecyl sulfate-resistant oligomers on polyacrylamide gels. Incorporation of small amounts (10(-10) to 10(-11) M) of purified protein K into artificial lipid bilayers resulted in an increase, by many orders of magnitude, in membrane conductance. The increased conductance resulted from the formation of large, water-filled, ion-permeable channels exhibiting single-channel conductance in 1.0 M KCl of 1.83 nS. The membrane conductance showed a linear relationship between current and applied voltage and was not voltage induced or regulated. The channel was permeable to large organic ions (e.g., Tris+ Cl-) and, based upon a pore length of 7.5 nm, a minimum channel diameter of 1.2 nm was estimated; these properties resemble values for other enteric porins. The possible biological role of the pores produced by protein K is discussed.